2005
DOI: 10.1007/s10533-004-0566-3
|View full text |Cite
|
Sign up to set email alerts
|

Soil CO2 efflux in loblolly pine (Pinus taeda L.) plantations on the Virginia Piedmont and South Carolina Coastal Plain over a rotation-length chronosequence

Abstract: We measured soil surface CO 2 efflux (F s ) in loblolly pine stands (Pinus taeda L.) located on the Virginia Piedmont (VA) and South Carolina Coastal Plain (SC) in efforts to assess the impact climate, productivity, and cultural practices have on F s in the managed loblolly pine ecosystem. The effect of stand age on F s was examined using a replicated chronosequence approach in which stands ranging from 1 to 25 years since planting were investigated. Soil CO 2 efflux was measured on both VA and SC sites for ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 49 publications
(84 reference statements)
1
40
1
2
Order By: Relevance
“…Our estimates of total soil CO 2 efflux ranged from 2.1 to 12.1 mmol CO 2 m À2 s À1 and were consistent with rates measured by others for mature loblolly pine stands (Selig, 2003;Wiseman and Seiler, 2004;Butnor et al, 2005;Gough et al, 2005). Perhaps because of the limited range in soil temperature during this study, temperature explained very little of the variation in F S or R H .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our estimates of total soil CO 2 efflux ranged from 2.1 to 12.1 mmol CO 2 m À2 s À1 and were consistent with rates measured by others for mature loblolly pine stands (Selig, 2003;Wiseman and Seiler, 2004;Butnor et al, 2005;Gough et al, 2005). Perhaps because of the limited range in soil temperature during this study, temperature explained very little of the variation in F S or R H .…”
Section: Discussionsupporting
confidence: 91%
“…Site preparation (i.e., ditching and bedding) can lead to improved soil aeration, seedling survival, and accelerate early growth (Burger and Pritchett, 1988;Andrews, 1993;Allen and Lein, 1998;Wheeler et al, 2002;Miwa et al, 2004). Short-term site preparation treatments, such as bedding, can provide an enhanced soil environment (aeration, temperature, and moisture) as well as incorporate OM into the mineral soil, leading to increased decomposition of soil OM, and, consequently, increased F S and R H in the years immediately following site preparation (Ewel et al, 1987;Trettin et al, 1996;Gough et al, 2005). www.elsevier.com/locate/foreco Forest Ecology and Management 234 (2006) [363][364][365][366][367][368][369] Pine plantations in the Southeastern United States currently comprise approximately 13 million ha, and are forecasted to increase to about 22 million ha by 2040 (Wear and Greis, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although theory predicts a possible decline in R S from middle-aged to older forests [12], several studies have reported positive relationships between stand age and soil respiration rates spanning various stages of forest development [6,13,16,17]. We found no evidence of either of these patterns, but we did find that soil respiration rates were often lower in Y31 than in the other stands during the middle of the growing season, particularly in July and August when soil temperatures were highest.…”
Section: Stand Age Effects On Soil Respirationcontrasting
confidence: 85%
“…A study by Gough et al [34] reported seasonal R S rates between 1 and 5 µmol CO 2 m −2 ·s −1 in a four-year-old loblolly pine stand on the Virginia Piedmont. Another study by Wiseman and Seiler [35] reported maximum R S of 4 µmol CO 2 m −2 ·s −1 in 1-to 2-year-old loblolly pine stands and 7 µmol CO 2 m −2 ·s −1 in 20-to 25-year-old loblolly pine stands located on the Virginia Piedmont.…”
Section: Soil Co 2 Effluxmentioning
confidence: 99%